The Psychosocial Adjustments of Broken Home Children and Their Academic Performance in Selected Secondary Schools in Marawi City - Faranessa M Ditucalan (RIRAI Publisher, 2026)
This study aimed to understand the psychosocial adjustments and academic performance of broken home children in selected secondary schools in Marawi City and the variables influencing these responses. Using a cross-sectional survey and evaluation research design with 151 respondents, data were gathered through a researcher-made questionnaire. Findings showed that respondents often adjusted emotionally (WM=3.04; SD=0.8785) and personally through prayer (WM=2.98; SD=0.9965), while social adjustments were sometimes evident (WM=2.87; SD=1.0412). Academically, respondents always showed motivation in studies (WM=3.30; SD=0.7983), often demonstrated interest in lessons (WM=3.19; SD=0.8463), attended classes regularly (WM=3.27; SD=0.9233), and 45.03% achieved satisfactory CGPA. Psychosocial adjustments were significantly related to academic performance. The study concluded that adolescents can adapt positively despite parental divorce, performing well academically when able to adjust personally, socially, and emotionally. Recommendations include continued parental support, guidance, open communication, and community involvement to help broken home children overcome challenges and succeed academically.